Effects of muscle mass and muscle quality estimated by phase angle on functional outcomes in older patients undergoing rehabilitation: A prospective cohort study. (29th October 2022) - Ohtsubo, Takuro; Nozoe, Masafumi; Kanai, Masashi; Ueno, Katsuhiro; Nakayama, Mai
Abstract: Background: Both skeletal muscle mass and muscle quality are important predictors of poor prognosis in older patients. However, the effects of muscle mass and muscle quality estimated by the phase angle (PhA) on functional outcomes in older patients undergoing rehabilitation have yet to be reported. This study aimed to investigate whether appendicular skeletal muscle index (SMI) and muscle quality estimated by PhA were independently associated with activities of daily living (ADL) and physical function in older patients undergoing rehabilitation. Methods: This prospective cohort study included older patients in a subacute rehabilitation hospital ( n = 443). Baseline SMI and PhA were measured using bioelectrical impedance analysis, and low SMI or low PhA were determined using each cutoff value. The primary outcomes were ADL abilities measured using the functional independence measure for motor function (FIM‐M) score and physical function measured using the short physical performance battery (SPPB) score at hospital discharge. Association between low SMI and low PhA and FIM‐M or SPPB scores at discharge were determined using multiple regression analysis adjusted for confounding factors. Results: There were significant differences between the normal‐ and low‐PhA groups in the FIM‐M and SPPB scores at discharge ( P < 0.001). In multiple regression analysis, low PhA was independently associated with FIM‐M ( β = −0.109, P = 0.013) and SPPB scores ( β = 0.535, P < 0.001) at discharge; however, low SMI was not independently associated with these functional outcomes. Conclusion: Decreased muscle quality estimated by the PhA was independently associated with poor ADL abilities and poor physical function in older patients undergoing rehabilitation.